2016
DOI: 10.1111/jai.13215
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight and length-length relationships for four freshwater fish species from Gölbaşı Lake (Hatay), Turkey

Abstract: Summary Length–weight and length–length relationships are presented for four freshwater fish species [Liza abu (Heckel, 1843), Aphanius mento (Heckel, 1843), Oxynoemacheilus hamwii (Krupp & Schneider, 1991) and Chondrostoma kinzelbachi Krupp, 1985] captured in Gölbaşı Lake, Hatay, Anatolia. No information regarding length–weight relationships was reported previously in FishBase for C. kinzelbachi, A. mento and O. hamwii. Specimens were obtained from January to May 2012 using electrofishing and cast nets. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
3
3
0
Order By: Relevance
“…In addition, the comparison of length-weight relationship parameters obtained by various researchers from different regions for other fish species belonging to the genus Cobitis and Oxynamecheilus are given in Table 4 and Table 5. Based on previously reported studies, positive allometry (+) and negative allometry (-) were observed in O. hamvii from Turkey (Table 3). Positive allometric growth (b= 3.520) determined in this study was in accordance with results reported in the previous study (Özcan & Altun, 2016). On the contrary, Birecikligil & Ciçek (2011) from Euphrates and Orontes Rivers of Turkey has reported negative allometric growth (b= 2.660).…”
Section: Resultssupporting
confidence: 91%
“…In addition, the comparison of length-weight relationship parameters obtained by various researchers from different regions for other fish species belonging to the genus Cobitis and Oxynamecheilus are given in Table 4 and Table 5. Based on previously reported studies, positive allometry (+) and negative allometry (-) were observed in O. hamvii from Turkey (Table 3). Positive allometric growth (b= 3.520) determined in this study was in accordance with results reported in the previous study (Özcan & Altun, 2016). On the contrary, Birecikligil & Ciçek (2011) from Euphrates and Orontes Rivers of Turkey has reported negative allometric growth (b= 2.660).…”
Section: Resultssupporting
confidence: 91%
“…Allometric growth of Oxynoemacheilus genus determined in this study was in accordance with results reported in earlier studies (Gaygusuz et al, 2012;Erk'akan et al, 2013;Erk'akan et al, 2014;Innal et al, 2015;Birekcikligil et al, 2016;Özcan & Altun, 2016).…”
Section: Length Frequency Distribution Of O Anatolicus Is Given In Tablesupporting
confidence: 92%
“…The total length of O. anatolicus ranged from 2.5 to 8.6 cm, which fits well within the known values (Table 3) while the minimum length observed in this study was close to the value reported for Oxynoemacheilus angorae from the Kızılırmak River Basin (Birekcikliğil et al, 2016). The maximum length was closer to known reported values for some species; Oxynoemacheilus angorae from the Kızılırmak River Basin (Birekcikliğil et al, 2016) and Sögütözü Beynam (Erk'akan et al, 2014), for Oxynoemacheilus hamwii from Gölbaşı Lake (Özcan & Altun, 2016), for Oxynoemacheilus mesudae from Küfe Creek (Erk'akan et al, 2014), for Oxynoemacheilus samanticus from Karaboğaz Creek (Erk'akan et al, 2014), for Oxynoemacheilus theophilii from Yiğitler Creek (Innal et al, 2015). In population structure, female individuals of O. anatolicus showed wider length range, mean length and weight than males.…”
Section: Length Frequency Distribution Of O Anatolicus Is Given In Tablesupporting
confidence: 79%
See 1 more Smart Citation
“…The length-weight relationships (LWRs) were determined by the method of least squares using the equation W = aL b (Wang et al, 2012), where "W" was the weight of the samples in gram and "L" the length of the samples in centimeter, "a" parameter is the intercept and "b" parameter is the slope.…”
Section: Length-weight Relationshipmentioning
confidence: 99%